Future Weakening of the ENSO Ocean Carbon Buffer Under Anthropogenic Forcing. Issue 18 (21st September 2021) - Liao, Enhui; Resplandy, Laure; Liu, Junjie; Bowman, Kevin W.
Abstract: The El Niño Southern Oscillation (ENSO) is the largest driver of atmospheric CO2 interannual variability. The equatorial Pacific Ocean, which is a natural source of CO2 to the atmosphere, acts as a buffer of the terrestrial variations by releasing less CO2 during El Niño events and releasing more CO2 during La Niña events. Here, we examine how this ocean carbon buffer will respond to high anthropogenic emissions using Earth system models from Coupled Model Intercomparison Project Phase 6. The models project weaker ocean CO2 flux anomalies in the future due to two main factors: a stronger compensation between thermal and nonthermal changes in ocean biogeochemistry (55% of signal) and a weaker influence of ENSO on the CO2 transfer across the air‐sea interface (10%–25% of signal). The ocean would no longer buffer the land response to ENSO, and could even reinforce its impact on atmospheric CO2, amplifying the atmospheric carbon variability on interannual timescales. Plain Language Summary: The El Niño Southern Oscillation (ENSO) is the main source of year‐to‐year natural variability in atmospheric CO2 . ENSO cycles impact the carbon uptake by the land biosphere and ocean and modulate the fraction of anthropogenic CO2 emissions that remains in the atmosphere. The equatorial Pacific Ocean can partly offset the terrestrial effect by releasing less CO2 during El Niño events and releasing more CO2 during La Niña events. We examine the ocean carbon response to ENSO under the business‐as‐usual emission scenario using the latest generation of Earth system models. The models project that the ocean will no longer act as a buffer in the future, but reinforce the variations of atmospheric CO2 tied to the land. Key Points: Earth system models project weaker ocean CO2 flux anomalies in the Pacific Ocean during future El Niño and La Niña events This weakening comes from the compensation between thermal and nonthermal changes in ocean p CO2 and weaker CO2 transfer at ocean surface The tropical Pacific Ocean would no longer buffer the land response to El Niño Southern Oscillation and could amplify atmospheric CO2 interannual variability